PENGARUH MEDIA TANAM DAN PEMANGKASAN PUCUK TERHADAP PERTUMBUHAN VEGETATIF TAPAK DARA (Catharanthus roseus (L.) G. Don) - Nurhayu Malik; Indrawati Indrawati; St. Mantasia (Universitas Halu Oleo, 2022)
This study aimed to determine the effect of planting media and shoot pruning on the vegetative growth of the tapak dara (Catharanthus roseus (L.) G. Don) plant. The research method was factorial completely randomized design (CRD) with a combination of planting media and shoot pruning. The treatments were ultisol soil media (M0), a mixture of husk charcoal in a ratio of 1:1 (M1) and 1:2 (M2) with a pruning frequency of no shoot pruning (P0), 1 time pruning (P2) and 2 shoots pruning (P2), so that 9 treatment combinations were obtained, namely M0P0, M0P1, M0P2, M1P0, M1P1, M1P2, M2P0, M2P1 and M2P2, each treatment consisted of 3 replications so that the all sample of media used in this study was 27 polybags. Parameters observed in this study were vegetative growth including plant height (cm), number of branches, number of leaves (strands). The results showed that the planting medium and shoot pruning had a significant effect on the vegetative growth of the tapak dara (Catharanthus roseus (L) G. Don) plant which included plant height, number of branches and number of leaves, where the best plant height measurement was the M2P0 treatment with height the plant reaches 23.5 cm. The highest number of branches was produced in the M2P2 treatment with an average number of branches, which was 7.3. The highest number of leaves was in the M1P1 treatment with the number of leaves reaching 40 strands.